جودة الخدمة في تجارة التجزئة وأثرها على رضا العميل دراسة ميدانية على متاجر الألبسة الجاهزة بمدينة طرطوس - علي, سليمان; زريقا, ولاء (Latakia University Journal - Economic and Legal Sciences Series, 2013)
تلعب جودة الخدمة المقدمة في متاجر التجزئة دوراً محوريا في إرضاء العميل، وهذا البحث يهدف بشكل أساسي إلى دراسة أثر أبعاد جودة الخدمة المقدمة في متاجر الألبسة الجاهزة بمدينة طرطوس على رضا العميل وتحديد البعد الأكثر تأثيراً في تفسير الرضا، واستخدم الباحث مقياس جودة الخدمة بالتجزئة RSQM المطور من قبل (Dabholkar et al. (1996. وتبين من خلال الدراسة أن هناك علاقة إيجابية و مهمة بين التفاعل الشخصي ورضا العميل ويحتل مؤشر التفاعل الشخصي المرتبة الأولى بين أبعاد جودة الخدمة بالتجزئة من حيث التأثير على رضا العميل، كما أن العلاقة بين مؤشر السياسة العامة للمتجر ورضا العميل علاقة مهمة وإيجابية ويأتي بالمرتبة الثانية، أما العلاقة بين المظاهر المادية لمتجر الألبسة ورضا العميل هي علاقة مهمة وإيجابية أيضاً، والعلاقة بين مؤشر حل المشكلة ورضا العميل علاقة مهمة وإيجابية، أما البعد المتعلق بالاعتمادية ليس له أهمية على رضا العميل، وجودة الخدمة ككل تفسر ما نسبته (69%) من هذا الرضا. وأهم التوصيات التي توصل إليها الباحث، أنه يجب على تجار الألبسة في مدينة طرطوس إقامة أفضل العلاقات مع العملاء، وألا ينظروا للعميل كفرصة يجب اقتناصها، بل يجب كسب رضاه وولاءه. Service quality provided in retailing plays a pivotal role in satisfying customer, this research aims mainly to study the effect of the dimensions of quality of service provided in clothes stores in Tartous city on customer satisfaction and determine the dimension of the most influential in the interpretation of satisfaction, the researcher used measure of quality of service in retailing (RSQM) developer by (Dabholkar et al. 1996). The findings of this study shows that There is significant positive relationship between personal interaction and customer satisfaction and personal interaction variable occupies first place among retail service quality dimensions in terms of impact on customer satisfaction, while the relationship between the policy of clothes stores and customer satisfaction was found to be important and positive and comes in the second place, and the relationship between physical aspects and customer satisfaction was also found to be important and positive, solving the problem has a positive and important relationship with customer satisfaction and comes fourth, the dimension of reliability is not important to customer satisfaction and finally quality of service as a whole explain a rate (69% ) of customer satisfaction. The most important recommendations reached by the researcher, that the clothing traders in Tartous City must establish better relations with customers, and not to look at the client as an opportunity must be seize, but must gain hi satisfaction and loyalty.